Carbon Emissions Disclosure as Mechanism to Increase Environmental Performance and Control of Idiosyncratic Risk: How They Impact Firm Value - Fransiskus Eduardus Daromes; Suwandi Ng; Novita Wijaya (Universitas Pasundan, 2020)
This research attempts to investigate the predictive effect of carbon emissions disclosure on firm value both directly and through environmental performance and idiosyncratic risk. With data collected from all non-financial high-profile companies listed on the Indonesia Stock Exchange and testing through path analysis, findings reveal that carbon emissions disclosure has a positive significant effect on environmental performance, but not on idiosyncratic risk and firm value. Further statistics testing showed that both idiosyncratic risk and environmental performance have a positive and significant effect on firm value. We also used Sobel testing to test mediation role of environmental performance and idiosyncratic risk on the effect of carbon emissions disclosure on firm value. The results show that environmental performance plays a mediating role whereas idiosyncratic risk does not. The implications of this research study are discussed from both theoretical and managerial perspectives.